SIK2: A novel negative feedback regulator of FGF signaling - Kuser-Abali, Gamze; Ugurlu-Bayarslan, Asli; Yilmaz, Yeliz; Ozcan, Ferruh; Karaer, Funda; Bugra, Kuyas (Cold Spring Harbor Laboratory, 2023)
AbstractA wide range of cells respond to FGF2 by proliferation via activation of the Ras/ERK pathway. In this study we explored the potential involvement of serine/threonine kinase SIK2 in this cascade within retinal Müller glia. We found that SIK2 phosphorylation status and activity is modulated in an FGF2-dependent manner, possibly via ERK. With SIK2 downregulation we observed enhanced ERK activation with delayed attenuation and increased cell proliferation, while SIK2 overexpression hampered FGF-dependent ERK activation. In vitro kinase and site directed mutagenesis studies indicated that SIK2 targets the pathway element Gab1 on Ser266. This phosphorylation event weakens Gab1 interactions with its partners Grb2 and Shp2. Collectively, our results suggest that during FGF dependent proliferation process ERK-mediated activation of SIK2 targets Gab1, resulting in downregulation of the Ras/ERK cascade in a feedback loop.